1994
DOI: 10.1111/j.1365-2249.1994.tb06114.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced interferon-gamma (IFN-γ) secretion with increased IFN-γ mRNA expression in atopic dermatitis: evidence for a post-transcriptional defect

Abstract: SUMMARYReduced secretioti of IFN-7 in atopic itidividuals has been implicated iti the pathogenesis of disease, though the mechanisms leading to this reduced secretion have nol been elucidated. As production of IFN-'y has been shown to be predominantly regulated by its rate of transcription, expression of IFN-7 mRNA was examined in atopic children and in age-matched, non-atopic controls by polymerase chain reaction (PCR)-assisted mRNA amplification. Children with atopic dermatitis were found to have constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Furthermore, interferon‐ γ is required for the induction of antibodies against polysaccharide epitopes (8, 18). Peripheral blood lymphocytes of atopic children produce less interferon‐ γ (30) but their defective interferon‐ γ production has been reversed by L. rhamnosus GG (1). Improved Hib antibody production of high‐risk infants in our probiotic group may thus reflect accelerated immune system maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interferon‐ γ is required for the induction of antibodies against polysaccharide epitopes (8, 18). Peripheral blood lymphocytes of atopic children produce less interferon‐ γ (30) but their defective interferon‐ γ production has been reversed by L. rhamnosus GG (1). Improved Hib antibody production of high‐risk infants in our probiotic group may thus reflect accelerated immune system maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Our present fmding of increased constitutive and stimulated IL-4 mRNA expression in PBMC from patients witb AD supports an increased Th2 aetivity in AD. However, we bave also examined iEN-'y mRNA expression in these patients, and found increased spontaneous iFN-7 expression witb detectable mRNA expression in six of tbe eigbt atopic patients [6]. A recent study of active atopic dermatitis skin lesions similarly reported more frequent expression of iFN-7 mRNA (13 of 15 patients) compared with iL-4 mRNA (four of 15 patients), as well as greater expression of iFN-7 mRNA than lL-4 mRNA in patients expressing bolh cytokines [44].…”
Section: Djscvjssionmentioning
confidence: 92%
“…The fmding that anti-lL-4 antibody inhibits this spontaneous IgE production in peripheral blood mononuclear cell (PBMC) cultures from atopic individuals suggests that spontaneous TL-4 production in these cultures may contribute to the IgE synthesis [2,4], Spontaneous generation of other cytokines has been reported in atopic individuals. We have recently found increased interferon-gamma (lFN-7)-producing cells [5] and constitutive transcription of IFN-7 mRNA [6] in unstimulated PBMC cultures from children with atopic dermatitis (AD), and spontaneous secretion of lL-6 by T cells from adults with AD was documented by Toshitani et al [1]. These fmdings suggested that T cells had been activated in vivo.…”
Section: Introdljctionmentioning
confidence: 99%
“…Interestingly, the IFN-Υ level fails to recover upon IL-2 stimulation, suggesting a potential intrinsic dysfunction (226). Although IFN-Υ mRNA transcripts are elevated, its release is reduced (227). Other studies found that IFN-Υ is spontaneously produced intracellularly, and that IFN-Υ-producing cells are rather increased in AD.…”
Section: Interferon-ϒmentioning
confidence: 98%